If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18p + 12q + p + -6q + -6p = 0 Reorder the terms: 18p + p + -6p + 12q + -6q = 0 Combine like terms: 18p + p = 19p 19p + -6p + 12q + -6q = 0 Combine like terms: 19p + -6p = 13p 13p + 12q + -6q = 0 Combine like terms: 12q + -6q = 6q 13p + 6q = 0 Solving 13p + 6q = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-6q' to each side of the equation. 13p + 6q + -6q = 0 + -6q Combine like terms: 6q + -6q = 0 13p + 0 = 0 + -6q 13p = 0 + -6q Remove the zero: 13p = -6q Divide each side by '13'. p = -0.4615384615q Simplifying p = -0.4615384615q
| 11-3x=33x+15 | | 65-4x=5x+18 | | (6w+5)-w= | | log(x)*25=2 | | 5a-1=11 | | 16=12x-1 | | 3*1.6=x | | 11a+15b+4c+3c-6b-5a= | | 0.05x+.06(20000-x)=1740 | | 20p+17q+p-7q-5p= | | 14m+6n-5m+8n= | | X^2-4=1 | | 8x-3=9x+7 | | 2x^2-3x-20= | | 2r+8=-1 | | -4a+24+7a=3a-8a | | 5x+2x-3=24 | | 7/8x-3+1/4x=5/24x+1/6 | | 12a+11b+2c+6c-2b-4a= | | 14x^3+35x-7= | | x/7+3=-4 | | 15x^2+55x= | | c-21c+21=0 | | -3=-6w-7 | | -90=7x+3x | | 3x^7+21x^4-54x^3= | | x-9x+8=0 | | x/2=-10+2 | | 3.5x-5+3=-15 | | a(13)=5-2(15) | | -8n+16=-4n-16 | | y=30+25x |